Informed consent prior to surgical treatment - Schlegel, Karl Andreas (Implantologie, 2019)
Legal standards in medicine should shelter the patient, are often tightening the decision making scope of the doctor and are due to the legal wording hard to understand for the practitioner. The following article tries to wrap up the essential legal aspects for the GP.
CRIS-Team WoS Importer:2019-05-24